PERSIAPAN SISWA DALAM MEMASUKI DUNIA KERJA DAN IMPLIKASINYA TERHADAP PELAYANAN BIMBINGAN DAN KONSELING - Sari, Lidia Herlin Permata (Konselor, 2013)
A career preparations programs is indeed needed by every individual to help them developing personal career. The best period of this program to be given is school period. The main target is student which will face the profesional world of work or job, soon after graduating. The preparation covers some factors that affect dominantly in the succesful of individual career. The research is done to describe the preparation of student before starting their career. The programs include, understanding the identity of job characteristic, understanding of personal potential, understanding of physical and psycho. Generally, the current students career preparations program is categorized in good category. Despite that, still required some additions, they are, informations service, privat personal, counseling service,group service, and group guidance counseling service. Keywords: Preparations, starting their career.